Listening to music during intranasal (es)ketamine therapy in patients with treatment-resistant depression correlates with better tolerability and reduced anxiety - Hauser, Johannes; Sarlon, Jan; Liwinski, Timur; Brühl, Annette B.; Lang, Undine E. (Frontiers in Psychiatry, 2024)
Background: Although the effectiveness of (es)ketamine for therapy-resistant depression (TRD) has been established, potential treatment-limiting factors include side effects like dissociation, anxiety, or elevated blood pressure. Music can reduce stress and negative emotions such as anxiety. This study aimed to investigate the impact of listening to music during intranasal (es)ketamine administration on both tolerability and efficacy.Methods: Records of 494 sessions (of 37 patients) with intranasal (es)ketamine administration, each containing data of blood pressure measurements, DSS-IV (dissociation symptoms scale-IV), anxiety and euphoria analogue scale, MADRS (Montgomery-Åsberg Depression Rating Scale) and BDI (Beck's Depression Inventory) were evaluated.The between-group analysis, comparing participants who listened to music with those who did not, revealed significant differences in the administered dose (p-value: 0.003, mean: 131.5 mg with music vs. 116.7 mg without music), scores on the DSS Item 1 (p-value: 0.005, mean: 3 points vs. 2.4 points), levels of anxiety (p-value: <0.001, mean: 0.4 points vs. 1.4 points), and measurements of maximal systolic blood pressure after administration (p-value: 0.017, mean: 137.9 mmHg vs. 140.3 mmHg). Listening to music had no impact on the MARDS-change score between the sessions.Limitations: Key limitations include a non-randomized naturalistic design and the non-standardized selection of music, which was based on individual patient preferences.Conclusions: Listening to music during intranasal (es)ketamine therapy appears to be linked to reduced anxiety and lower blood pressure, stable or increased dissociation levels, and improved tolerance for higher doses. These findings could potentially contribute to the optimization of (es)ketamine therapy, both in terms of treatment efficacy and managing side effects.